2022
DOI: 10.1051/0004-6361/202243866
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the HII region escape fraction of ionizing photons from infrared emission lines in metal-poor star-forming dwarf galaxies

Abstract: Context. Local metal-poor galaxies stand as ideal laboratories to probe the properties of the interstellar medium (ISM) in chemically unevolved conditions. Detailed studies of this primitive ISM can help gain insights on the physics of the first primordial galaxies that may be responsible for the Reionization. Quantifying the ISM porosity to ionizing photons in nearby galaxies may improve our understanding of the mechanisms leading to Lyman Continuum photons leakage from galaxies. The wealth of infrared (IR) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 217 publications
1
10
0
Order By: Relevance
“…The positive correlation between the two quantities is in qualitative agreement with the predictions of Inoue et al (2016), Katz et al (2022), andRamambason et al (2022).…”
Section: [O Iii]/[c Ii]-f Esc Relationsupporting
confidence: 84%
See 1 more Smart Citation
“…The positive correlation between the two quantities is in qualitative agreement with the predictions of Inoue et al (2016), Katz et al (2022), andRamambason et al (2022).…”
Section: [O Iii]/[c Ii]-f Esc Relationsupporting
confidence: 84%
“…The authors found that the parameter mostly affecting the line ratio is the burstiness. More recently, Ramambason et al (2022) examined ISM properties of a local sample of the Herschel Dwarf Galaxy Survey (HDGS, Madden et al 2013;Cormier et al 2015) using a grid of models of H ii regions and photo-dissociated regions. The authors have also found a positive correlation between [O iii]/[C ii]and predicted f esc .…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of works in the literature exploring the efficacy of X-ray sources in the production of high-energy ionizing photons, with a particular recent emphasis on the X-ray contribution to production of He II λ4686 in high-redshift galaxies and their analogs (e.g., Kehrig et al 2018Kehrig et al , 2021Schaerer et al 2019;Senchyna et al 2020;Simmonds et al 2021;Kovlakas et al 2022;Oskinova & Schaerer 2022;Ramambason et al 2022;Umeda et al 2022). The most recent investigations fall broadly into two categories:…”
Section: Comparison With Recent Literaturementioning
confidence: 99%
“…We note that fixing R and varying only ionizing flux means certain geometric effects are not accounted for in these models; such geometrical effects can substantially change both high-ionization and neutral line emission (e.g.,Ramambason et al 2022). …”
mentioning
confidence: 99%
“…The large predicted Hα fluxes compared to the observed values, particularly for SBS1 and Kiso3867, raise the possibility that some of the expected LyC photons are being absorbed by dust or escaping the observed HII regions and diffuse Hα. Low-metallicity galaxies like these typically have more LyC escape (Ramambason et al 2022). Deeper images will be required to determine if escaping LyC is ionizing an extended halo around the galaxies, or is possibly escaping the galaxies altogether.…”
Section: Comparison Between Observed Hα Flux and Predictions From Sta...mentioning
confidence: 99%